2009 4th International Conference on Recent Advances in Space Technologies 2009
DOI: 10.1109/rast.2009.5158292
|View full text |Cite
|
Sign up to set email alerts
|

Design and prototype of a flight microstrip antennas for the Pico satellite ERPSat-1

Abstract: Small satellites, accomplished by new technologies, allowed the achievement of many tasks and experiments in space. In this context, Pico satellites team of Research Group on Intelligent Machines laboratory of the engineering school of Sfax, Tunisia, has designed and prototyped Microstrip antennas for the first Tunisian Pico satellite ERPSat-1 use. Its resonant frequency is 2.4 GHz. The various losses like atmospheric, free space, Ionosphere and rain losses are taken in consideration. Atmospheric and free spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
0
6
0
1
Order By: Relevance
“…The next study deals specifically with planar antennas targetting a CubeSat programme. (Hamrouni et al, 2009) designed and prototyped two microstrip antennas on a 1.6 mm-tall substrate. The antennas were intended for use on the first Tunisian pico-satelite ERPSat-1 and operated at 2.4 GHz (S-band).…”
Section: Planar Antennas For Modern Small Satellitesmentioning
confidence: 99%
See 2 more Smart Citations
“…The next study deals specifically with planar antennas targetting a CubeSat programme. (Hamrouni et al, 2009) designed and prototyped two microstrip antennas on a 1.6 mm-tall substrate. The antennas were intended for use on the first Tunisian pico-satelite ERPSat-1 and operated at 2.4 GHz (S-band).…”
Section: Planar Antennas For Modern Small Satellitesmentioning
confidence: 99%
“…At the other end of the design spectrum, the work by (Muchalski et al, 2004) is a typical example of how suspended, electrically large patches can exhibit quite significant bandwidths. Furthermore, resonant-size patches can produce gains in the range 4-6.5 dBi and bandwidths of a few percent (Gao et al, 2008;Hamrouni et al, 2009;Maqsood et al, 2010). On the other hand, 3-D structures consisting of folded and stacked radiating parts offer moderate bandwidths and gains combined, and can even become electrically small (Lee & Woo, 2008).…”
Section: Comparison With Existing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These antennas rest on a substrate with a permittivity equal to 4.32 and thickness H equal to 1.6 mm. After simulations and test, the team found that the antenna resonant frequency is 2.4 GHz and has a directive radiated pattern and a band width of 70 MHz [13]. One of these antennas is shown in the following figure: The energy required to operate the satellite will be provided by tiny solar panels affixed to the surface of the cube ( Figure 7).…”
Section: Erpsat-1 Systemmentioning
confidence: 99%
“…Το ηλεκτρικό μέγεθος υπολογίστηκε στο (ka) lower = 1.39 rad.Η επόμενη μελέτη αφορά ειδικά σε επίπεδη κεραία για το πρόγραμμα CubeSat. Οι Hamrouni et al[276] σχεδίασαν και κατασκεύασαν δύο μικροταινιακές κεραίες πάνω σε υπόστρωμα ύψους 1.6 mm. Οι κεραίες προορίζονται για τον πρώτο pico-δορυφόρο της Τυνησίας, τον ERPSat-1, και λειτουργούν στα 2.4 GHz (S-band).…”
unclassified